Immediate and delayed photoactivation of self-adhesive resin cements and retention of glass-fiber posts - André Luis Faria-e-Silva; Aline Carvalho Peixoto; Marcela Gonçalves Borges; Murilo de Sousa Menezes; Rafael Ratto de Moraes (Brazilian Oral Research, 2014)
The aim of this study was to evaluate the effect of immediate and delayed photoactivation of self-adhesive resin cements (SARCs) on the retention of glass-fiber posts luted into root canals. Bovine incisors were endodontically treated, and post holes of 9 mm in depth were prepared. Fiber posts were luted using one of two SARCs, BisCem(r) (Bisco Inc., Schaumburg, USA) or RelyX Unicem clicker (3M ESPE, Saint Paul, USA), or a regular (etch-and-rinse) resin cement (AllCem; FGM, Joinvile, Brazil). Photoactivation was performed immediately, or at 5 or 10 min after cementation. Root/post specimens were transversely sectioned 7 days after luting into 1-mm-thick slices, which were submitted to push-out testing in a mechanical testing machine. Bond strength data were analyzed by two-way ANOVA and Student-Newman-Keuls' method (α = 0.05). Immediate photoactivation resulted in the highest bond strength for Unicem. BisCem(r) demonstrated higher bond strength values when photoactivated after a 10-min delay. Immediate photoactivation yielded the lowest bond strengths for AllCem, although no differences in bond strength were observed between photoactivation delayed by 5 and 10 min. In conclusion, the moment of resin cement photoactivation may affect the intraradicular retention of fiber posts, depending upon the resin cement used for luting.